Voluntary Peer Review of Consumer Protection Law and Policy - Thailand - United Nations Conference on Trade; Development (United Nations, 2022)
General Assembly resolution 70/186 mandates the Intergovernmental Group of Experts on Consumer Protection Law and Policy to conduct voluntary peer reviews on consumer protection law and policy. The purpose of voluntary peer reviews in this field is to provide an external and independent assessment of the effectiveness of consumer protection law and policy in a given country; to identify the challenges to be addressed and areas to be improved in the legal and institutional frameworks, thereby contributing to enhancing quality, efficiency and consumer protection regimes; to assess the consumer protection awareness of relevant stakeholders and their contributions in this area; to formulate and recommend appropriate measures, designed in consideration of the economic and developmental particularities of each country, to address these challenges; and, where appropriate, to assist countries in implementing the recommendations by developing a capacity-building project in consultation with the country concerned. The present publication serves as basis for the Voluntary Peer Review on Consumer Protection Law and Policy of Thailand.